Structure of mycoses of the skin and its appendices in HIV-infected patients - V.D. Moskaliuk; I.I. Kravchuk; Yu.O. Randiuk; I.V. Balaniuk (Medičnì Perspektivi)
The spread of HIV infection is one of the most pressing problems of modern health care. The purpose of the work is to analyze the structure of the disease on the surface of the skin and its appendages by the nosological forms in HIV-infected persons and to establish a possible correlation between the presence of fungal lesions. The data obtained from 801 patients who sought medical help at the «Chernivtsi Regional Medical Center for Socially Significant Diseases» for the period from 2018 to 2023 were analyzed. The diagnosis of HIV infection was established according to the International Classification of Diseases of the 10th revision (ICD-10) and verified by the detection of specific serological and molecular biological markers of HIV. Mycological examination included microscopy of pathological material and cultural diagnosis. Analysing the structure of the disease it was found that skin mycoses and its appendages were detected in 334 (41,7%) HIV-infected patients. The main part of such patients – 237 (71%) – did not receive antiretroviral therapy (ART). Accordingly, dermatomycosis was detected in only 97 people (29%) who were adherent to ART. The relative risk method confirms the assessment of the effect of ART on the frequency of combined forms of mycosis – RR=0.608, which indicates the obvious rarity of the event (mycosis of the skin and its appendages), compared to the group that did not receive ART. A statistically significant direct relationship was established between the presence of a fungal skin lesion and its applications and indicators of HIV load in the blood – r=0.421...0.460 at p<0.001, as well as the duration of HIV infection – r=0.573...0.611 at p<0.01 . In addition, there is a clear positive correlation of medium strength between the duration of HIV infection and the level of viremia – r=0.388...0.427 at p<0.01, as well as an inverse weak relationship with the number of CD4+-lymphocytes – r=-0.105. ..-0.204 at p<0.05. The number of CD4+-lymphocytes was expected to be in an inverse correlation of medium strength with the HIV load (r=-0.618...-0.682, p<0.01). The relative risk of the development of mycoses of the skin and its applications in HIV-infected patients under the condition of antiretroviral therapy is only 0.262 (0.225-0.298), which indicates an obvious rarity of the event, compared to the group that did not receive antiretroviral therapy. The majority of HIV-infected patients (62.3%) have a combination of several nosological forms of mycosis of the skin and its applications. A strong inverse relationship between the probability of developing combined forms of mycoses and receiving antiretroviral therapy was revealed – r=-0.719...-0.806 at p<0.001. In the absence of antiretroviral therapy, a statistically significant direct relationship was established between the presence of fungal lesions of the skin and its appendages and indicators of HIV load in the blood, as well as the duration of HIV infection.